Relationship FoMO and Nomophobia with Social Anxiety Symptoms in the Use of Social Media at UMP - Noer Islamyah Charini; Supriyadi Supriyadi (Proceedings Series on Health & Medical Sciences, 2024)
Background:Along with the increase in social media users, people are also starting to experience what is called social anxiety. This social anxiety is caused by feelilngs of worry or fear of the judgment of others. This causes individuals who experience social anxiety to try to avoid social situations so that they can avoid the negative judgments of other. Anxiety about the judgment of others in one of the main symptoms of social anxiety. In addition, people who frequently use social media tend to like to compare themselves with others. Method: This research is a quantitative study with a cross-sectional approach. The sample used in this study was undergraduate nursing students at Muhammadiyah University in Purwokerto with a total of 99 respondents. There were 3 instruments used in this study, namely the SAS-SMU questionnaire, the FoMO’s questionnaire, and the NMP-Q questionnaire. Results: The results of the analysis of the relationship using the chi-square statistical test found p=0.000(p<0.05),meaning that there is asignificant relationship between FoMO and symptoms of social anxiety in the use of socialmedia. The results of the relationship analysis using the chi-square statistical testfound p=0.001 (p<0.05), meaning that there is a significant relationship between Nomophobia and symptoms of social anxiety in the use of social media. Conclusion:There is a significant relationship between FoMO and symptoms ofsocial anxiety in using social media and there is also a significant relationship between Nomophobia and symptoms of social anxiety in using social media.